Water disinfection by the UVA/electro-Fenton process under near neutral conditions: Performance and mechanisms. (December 2022) - Chen, Xiongjian; Chen, Ziyu; Lin, Chun-Yan; Chen, Riyao; Huang, Peiwen; Jin, Yanchao
Abstract: An efficient and thorough water disinfection is critical for human health. In this study, UVA-LEDs, nitrilotriacetic acid (NTA) and a boron-doped diamond anode were respectively used as the UVA source, the iron chelator and the anode for the UVA/electro-Fenton (E-Fenton) reaction to treat wastewater. The disinfection performance of the UVA/E-Fenton had been investigated. The mechanisms of the E. coli inactivation had been clarified. The results showed that complete disinfection (about 5.6-log removal) could be achieved within 50 min at a certain condition due to the synergistic effort of the UVA, anodic oxidation and the electro-Fenton. The quenching experiments and the electron paramagnetic resonance (EPR) detection indicated that OH, O 2 − and 1 O2 play important roles for inactivating E. coli . The results of SEM images and genomic DNA electrophoresis suggested that both the cell structure and the DNA had been thoroughly destroyed during the UVA/E-Fenton process. Increasing the UVA irradiation, oxygen bubbling could improve the disinfection rate, while it also would increase the energy consumption. The appropriate Fe and NTA ratio was 1:2 to realize an efficient Fenton reaction under near neutral condition. Complete disinfection was also achieved within 50 min when it used for treating real wastewater. Thus, the UVA/E-Fenton process is a satisfied way for water disinfection. Graphical abstract: Image 1 Highlights: Both the cell structure and the bacterial genomic DNA was completely destroyed. Disinfection was achieved by the synergetic effort of UVA, BDD and electro-Fenton. Complete disinfection was achieved within 50 min under certain conditions. It revealed a satisfied performance in real wastewater disinfection.